Quail egg allergy with tolerance to chicken eggs: A case report - Ana Delgado-Prada, MD; Maria Jose Martinez-Martinez, MSc; Enrique Burches, MD, PhD; Angel Sastre-Sastre, MD; Fernando Pineda De La Losa, PhD; Celia Morales-Rubio, MD, PhD (Journal of Allergy and Clinical Immunology: Global)
This case study details a rare quail egg allergy with tolerance to chicken eggs in a 50-year-old woman.